Analysis of mutational dynamics at the DMPK (CTG)n locus identifies saliva as a suitable DNA sample source for genetic analysis in myotonic dystrophy type 1 - Corrales Acuña, Eyleen Vanessa (2019)
Genotype-to-phenotype correlation studies in myotonic dystrophy type 1 (DM1) have been confounded by the age-dependent, tissue-specific and expansion-biased features of somatic mosaicism of the expanded CTG repeat. Previously, we showed that by controlling for the confounding effects of somatic instability to estimate the progenitor allele CTG length in blood DNA, age at onset correlations could be significantly improved. To determine the suitability of saliva DNA as a source for genotyping, we used small pool-PCR to perform a detailed quantitative study of the somatic mutational dynamics of the CTG repeat in saliva and blood DNA from 40 DM1 patients. Notably, the modal allele length in saliva was only moderately higher in saliva and not as large as previously observed in most other tissues. The lower boundary of the allele distribution was also slightly higher in saliva than it was in blood DNA. However, the progenitor allele length estimated in blood explained more of the variation in age at onset than that estimated from saliva. Interestingly, although the modal allele length was slightly higher in saliva, the overall degree of somatic variation was typically lower than in blood DNA, revealing new insights into the tissue-specific dynamics of somatic mosaicism. These data indicate that saliva constitutes an accessible, non-invasive and suitable DNA sample source for performing genetic studies in DM1.